1994
DOI: 10.1007/bf00865463
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of retinol-binding protein excretion in normal children

Abstract: Retinol-binding protein (RBP) is a low molecular weight protein freely filtered at the glomerulus. The fractional tubular reabsorption of RBP is 99.97% and increased excretion is therefore a sensitive marker of tubular dysfunction. We obtained early-morning urine specimens from 151 well children, from newborn to 16 years of age. RBP was measured using an enzyme-linked immunosorbent assay, albumin by a radioimmunoassay and creatinine by a modified Jaffé reaction. Protein excretion was assessed by calculating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
4

Year Published

1995
1995
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 20 publications
0
18
0
4
Order By: Relevance
“…In the group of boys, but not in girls, a weak correlation was found between RBP excretion rate and age, whereas with the RBP/Cr ratio a weak, negative correlation with age was found only in girls. One study of younger children (< 10 years) showed that children in the 1st year of life have a considerably increased RBP/Cr ratio compared with older children [7]. In one recent study second-morning urine samples from 368 subjects from 6 to 16 years of age were used and an upper normal limit for urinary RBP/Cr similar to our results was reported [111.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In the group of boys, but not in girls, a weak correlation was found between RBP excretion rate and age, whereas with the RBP/Cr ratio a weak, negative correlation with age was found only in girls. One study of younger children (< 10 years) showed that children in the 1st year of life have a considerably increased RBP/Cr ratio compared with older children [7]. In one recent study second-morning urine samples from 368 subjects from 6 to 16 years of age were used and an upper normal limit for urinary RBP/Cr similar to our results was reported [111.…”
Section: Discussionmentioning
confidence: 67%
“…Bangstad and simple methods have been reported for RBP measurement [ 4 -6 ] , but RBP has not been widely used in kidney diseases in children. The available reference data are, with one exception [7], either based on small groups of subjects [ 8 -1 0 ] or briefly described [11]. The objective of our study was to obtain age-and pubertal stage-related values from 150 subjects of 1 0 -1 8 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, urinary lactate excretion correlated more strongly with urinary RBP than with other possible markers of metabolic control, including growth and plasma lipids. RBP is a low-molecular-weight protein synthesized by the liver that is normally filtered by the glomerulus and reabsorbed in the proximal renal tubule (Smith et al 1994). It is stable in acid urine, unlike flz-microglobulin, and therefore a reliable indicator of tubular function in the presence of lactic acidosis.…”
Section: Discussionmentioning
confidence: 99%
“…Controls were excluded if autoimmune disease, renal pathology or infection was diagnosed or clinically suspected. The literature has well-established data on tubular function in normal children [19] and those with nephrotic syndrome [18,20] and insulin-dependent diabetes mellitus [21].…”
Section: Methodsmentioning
confidence: 99%
“…Urine specimens taken from the controls were only analysed for RBP and NAG [18] (as this was the initial control protocol and they would have required blood to be taken for phosphate levels to calculate the TRP). All the urine samples were from the second episode of micturition during the day in order to avoid increased biochemical values found in early morning urine samples [19]. The NAG and RBP data were expressed as a ratio over urinary Cr in units of mmoles 2-methoxy-4-(2'nitrovinyl)-phenol (MNP)/h per millimole and micrograms per millimole, respectively.…”
Section: Methodsmentioning
confidence: 99%